217. Differences on GTV and PTV dose coverage for lung tumor stereotactic cyberknife treatments using Raytracing and MC algorithm: A retrospective study. (December 2018) - Mormile, M.; Iadanza, L.; Zambella, C.; Muto, P.
Abstract : Purpose: The aim of this work is to compare the coverage of GTVs and corresponding PTVs lung lesions in 86 patients treated at the National Tumor Institute of Naples "G. PASCALE", between January 2015 and June 2016, with CyberKnife using two different algorithms (Ray-tracing and MonteCarlo) with the same beams and the same number of monitor units per beam. Methods: The patients were treated with CyberKnife Linear accelerator in a ipofractionated radiotherapy regimen. We first divided the patients in two groups depending on tumor localization ( peripheral and central lesions) and then, in each group, we created three volume classes (GTV⩽10 cc; 10 cc <GTV<20 cc and GTV ⩾ 20 cc). In each class we compared the percentage volume coverage calculated, both with Ray Tracing and MonteCarlo, for GTV and corresponding PTV. Results: We noted that the prescription dose always cover more than 95% of both GTV and corresponding PTV in each volume class, not depending on tumor localization, using RayTracing Algorithm. On the contrary, using MonteCarlo algorithm, we noted a leakage in the coverage of GTV, but especially for PTV with undercoverage of until 80%, (probably due to the air included inside the volume) in each volume class for both peripheral and central lesions. Conclusions: The first follow up of this patients show, in many cases, reductions or disappearance of the lesions so, probably using MonteCarlo algorithm we should think of reducing the dose prescription. Furthermore, the costraints to organs at risk should be revised.